DAMPAK PROGRAM MBKM STUDI INDEPENDEN BERSERTIFIKAT “BE A DIGITAL EXPORTER” TERHADAP PENINGKATAN MAHASISWA MENJADI EKSPORTIR KOPI - Harahap, Mutia Aprilia (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2024)
Merdeka Belajar Campus Merdeka (MBKM) Certified Independent Study Program 'Be a Digital Exporter' at the Export School, this research aims to investigate the impact on increasing students' ability to become coffee exporters. The main focus of the research involved evaluating the digital skills improvement, mastery of the coffee industry, and certifications recognized by students taking part in the program. The research method uses descriptive qualitative data analysis, using direct observation methods in the field. The research results show that this program is successful in improving students' digital skills, providing in-depth knowledge of the coffee industry, and providing industry-recognized certification. This positive impact not only affects the level of success of individual students, but also has the potential to make a real contribution to the growth of the Indonesian coffee export industry. The conclusion of this research shows that the MBKM 'Be a Digital Exporter' Program not only creates digitally skilled coffee exporters, but also plays a role in shaping the future of the national coffee export industry.